Influence of pulping conditions on rice straw kraft pulp yield and screened rejects (Chemical Engineering Research Bulletin, 2026)
Although wood is the primary raw material for pulp and paper manufacturing, there is a growing interest in non-woody raw materials to meet the increasing demand of paper. Non-woody biomass rice straw is geographically abundant in South Asia which can be used as a potential raw material for pulp and paper production due to less chemical and shorter cooking time required in pulping process. The objective of this study was to investigate the effect of temperature and active alkali concentration (Na+) on pulp yield (%) and screened rejects (%) during the kraft pulping of rice straw. The kraft pulping was carried out at 15:1 liquor-to-straw ratio for an hour in a bomb digester with the variation of temperature from 80˚C to 120˚C and the active alkali (AA) concentration was increased up to 20%. At the temperature of 120˚C and with an AA charge of 20%, the screening process yielded a minimum pulp reject of 0.20%.However, the maximum pulp yield (55.16%) was achieved at the same temperature (120˚C) but reduced AA charge (16%) which are also the optimum pulping conditions for this study due to less chemicals (white liquor) and energy consumption. This optimum kraft pulping process can be used to convert more than half of the rice straw input into pulp with lower chemicals and energy use compared to the conventional wood-based pulping.Chemical Engineering Research Bulletin 24: (Issue 1) :30-40